Models and algorithms for professional development of education workers in the context of diversification of educational services - Luniachek, V. (Problems of Engineer-Pedagogical Education, 2020)
The problems of diversification of the process of advanced professional development of pedagogical staff in Ukraine caused by the entry into force of the Law of Ukraine "On Education" and the Resolution of the Cabinet of Ministers of Ukraine No. 800 of 21.08.2019 "On Some Issues of Professional Development of Research and Teaching Staff" are investigated in the paper. There is a lack of theoretical and methodological justification for this process, the need for its intensification. The materials of the analysis of scientific sources on the subject under review are presented starting from 2017, when there were fundamental changes in the normative-legal base of advanced training of teaching staff. Emphasis is placed on the development of models and algorithms for upgrading the skills of pedagogical staff, which will improve the dynamics of relevant processes by providing leaders and teachers with effective practical tools. In particular, a conceptual model of professional development of pedagogical staff in general secondary educational institutions is presented. A number of developed algorithms are suggested, including the algorithm of actions for general secondary education institutions authorities on managing the process of professional development of teaching staff. Particular attention is paid to the issues related to the modernization of training plans for teaching staff in the context of the introduction of a credit-accumulation system and empowering customers of educational services to choose topics for professional development based on the results of the process of self-assessment of their professional competence, as a top priority. The paper also provides a model of professional development of pedagogical staff through technology transfer, which creates new conditions and opportunities for objects and subjects of professional development. It is emphasized that there is a need to create powerful databases of pedagogical technologies developed in Ukraine and abroad and Web portals to improve the receipt of relevant information materials by consumers of training services for teaching staff.